Development of Slum District Application in The City of Bekasi Based on Web - Nur Hikmah; Nuke L Chusna; Ali Khumaidi (Jurnal Mantik, 2020)
The Government of Bekasi City through The Department of Public Housing, Settlement Areas and Lands (DISPERKIMTAN) has a program to reduce slum areas with the City Without Slum Program (KOTAKU). District data collection is currently being carried out manually by the team and then the data is entered into the information system which can only be accessed internally. Existing data are not updated quickly so it is sometimes difficult to determine policies related to development assistance. Rukun Tetangga (RT) and Rukun Warga (RW) are part of the government structure closest to the community so that if data collection is carried out by them, the data will be fast and updated. This slum application development was developed using the SDLC model of waterfall method, while the stages include analysis, system design, system implementation, and system testing. Testing the application using a black box and the results are in accordance with the scenario and expectations.